2022
DOI: 10.1002/ecs2.4224
|View full text |Cite
|
Sign up to set email alerts
|

Localized carry‐over effects of pond drying on survival, growth, and pathogen defenses in amphibians

Abstract: Climate change is increasing variability in precipitation patterns in many parts of the globe. Unpredictable changes in water availability can be particularly challenging for organisms that rely on precipitation-fed water sources for completing their life cycle, such as many amphibian species. Although developmental plasticity can mitigate the impacts of changing environments for some species, this strategy can come at a cost to other fitness-linked traits, such as immune function. We investigated localized va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 92 publications
(115 reference statements)
0
7
0
Order By: Relevance
“…For example, Enriquez‐Urzelai et al (2013) showed that developmental acceleration in response to drying in painted frogs ( Discoglossus pictus ) was observed only when food resources were not limited. Distinct populations and local adaptations could also drive the observed differences in developmental plasticity (Le Sage et al, 2022). Some populations may already have reached their maximum developmental rate, and thus are not able to respond to drying (Laurila et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Enriquez‐Urzelai et al (2013) showed that developmental acceleration in response to drying in painted frogs ( Discoglossus pictus ) was observed only when food resources were not limited. Distinct populations and local adaptations could also drive the observed differences in developmental plasticity (Le Sage et al, 2022). Some populations may already have reached their maximum developmental rate, and thus are not able to respond to drying (Laurila et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, co-stressors such as heat, pesticides, and parasites impact amphibian immune responses and can have synergistic effects on fecundity and post-recruitment survival (Kiesecker, 2002, Thompson et al, 2022. When anthropogenic stressors and abiotic factors synergize, the immune system is challenged (Kiesecker, 2011), and early stress experienced during development can affect resilience in later life stages (Kohli et al, 2019;Le Sage et al, 2022). Disease susceptibility can increase following herbicide exposure (Rohr et al, 2013), and lower microbiota diversity, a common result of pesticide exposure, is associated with reduced parasite resistance (Knutie et al, 2017).…”
Section: Stressor Interactionsmentioning
confidence: 99%
“…Distinguishing stagespecific endogenous variation in physiological processes enables anticipation of compromised physical condition in response to common stressors (Brooks and Kindsvater, 2022;Nolan et al, 2023). Here we focus on stressor impacts on transition between life (Denver, 2009;Duarte-Guterman et al, 2014;Thambirajah et al, 2019) GC ↑ to some xenobiotics (Burraco and Gomez-Mestre, 2016;Trudeau et al, 2020), environmental conditions (Sachs and Buchholz, 2019;Thambirajah et al, 2019), predators (Narayan et al, 2013) ; neurogenerative, oxidative, mitochondrial, teratological effects (Di Lorenzo et al, 2020) CS and TH levels in tissue or immersed water (Gabor et al, 2013a); tissue/ organism enzyme activity or DGE in AR, TR, tra, trb, dio2, dio3 (Thambirajah et al, 2022); ambient water assay; size at metamorphosis (Rowland et al, 2023); vitellogenin indicative of feminization (Venturino and de D'Angelo, 2005) Time to metamorphosis; cohort sex ratio; carryover to juvenile immunity, survival, fecundity (Kiesecker, 2002, Denver, 2009Kohli et al, 2019;Ruthsatz et al, 2020;Le Sage et al, 2022) Immunity Endocrine-driven development of immunity; immunosuppression at metamorphosis (Rollins-Smith, 2017)…”
Section: Lifestage-specific Physiologymentioning
confidence: 99%
“…On the other hand, the New Mexico spadefoot toad ( Spea multiplicata ) did not display carry-over effects of pond drying on immune function [ 29 ]. In two species of leopard frogs ( R. pipiens and Rana sphenocephala ), carry-over effects of shorter hydroperiods also included changes in host-associated microbiota [ 30 ], shifting to lower capacities to inhibit pathogen growth [ 31 ]. Thus, the effects of pond drying on the development of specific immune defences in postmetamorphic amphibians have been studied in a limited number of species, and further studies are needed.…”
Section: Amphibians Responding To Changing Environmentsmentioning
confidence: 99%